Classroom Action Research Investigation Conducted by Pre-Service Teachers Education Program - Siregar, Nurhafni; Nila Lestari; Nurmairina; Dinda Yarshal; Dewi Fitria; Harahap, Yulia Sari (Universitas Pendidikan Ganesha, 2025)
The Teacher Professional Education Study Program (PSPPG) has been organizing Pre-Service PPG since 2022. In semester II, students must carry out Classroom Action Research (PTK) and make a report based on the research results. This study analyzes the implementation of PTK in terms of the scope of the title, procedures, benefits and follow-up of PSPPG to improve students' PTK in the future. The study subjects were 18 English students and 25 Elementary School Teacher Education students at five schools where PPL was held. The research method used qualitative descriptive with data collection techniques through observation, questionnaires and interviews. The data collection instrument used observation sheets and questionnaires. The data analysis technique used qualitative and quantitative descriptive analysis. The analysis results showed that the implemented PTK reached a pretty good category. Students have carried out PTK according to the procedure. Specifically, it can be concluded that the output in the form of publications has not been maximized because it only reached 35%. In the future, PPG UMNAW needs to encourage 100% of students to have outputs in the form of publications in nationally accredited journals by issuing official regulations and a guidebook for publishing articles on PTK results.